Optimization of Ultrasonic-Assisted Extraction of Diene Urushiol from Lacquer Tree Leaves Using Response Surface Methodology - Fengming Xia; Haojiang He; Jize Ma; Yutian Jin; Qing Qiao; Peng Long; Ping Li; Rui Sun (Molecules)
Lacquer trees are an important economic tree species in China, and raw lacquer is its main secondary metabolite. Polyphenolic compounds are the primary components of raw lacquer, among which diene urushiol exhibits high inhibitory activity against the reverse transcriptase of acquired immunodeficiency syndrome (AIDS). Therefore, this study established and optimized the ultrasound-assisted extraction process of diene urushiol from lacquer tree leaves. Based on single-factor experiments on the number of extractions, extraction time, extraction temperature, and solvent to solid ratio, the Box–Behnken Design response surface methodology was employed to obtain the optimal extraction process, which included three extractions, an extraction time of 55 min, an extraction temperature of 50 °C, and a solvent to solid ratio of 10:1 mL/g. Under these conditions, the content of diene urushiol was 4.56 mg/g (FW), which bore no significant difference from the theoretical value of 4.69 mg/g (FW), indicating a good model fit. Therefore, response surface methodology (RSM) can be used to optimize the extraction process of diene urushiol from lacquer leaves. This method lays a solid foundation for the comprehensive development and utilization of lacquer tree resources.